Unlocking Satisfaction A Deep Dive into the Impact of Electronic Word-of-Mouth (EWOM) on Customer Satisfaction in the Realm of Digital Platform Services Offered by Takaful Operators - Ibrahim, Nur Izzati; Muhamat, Assoc Prof Dr Amirul Afif; Kamarul Bahrin, Nurul Fathiyah; Abdul Kamal, Nur Syazana (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
Takaful, as a distinctive form of Islamic insurance, plays a pivotal role in the financial landscape. In the era of digital transformation, takaful operators increasingly rely on digital platforms to deliver their services. This empirical study aims to investigates the dynamic relationship between Electronic Word-of-Mouth (EWOM) and customer satisfaction in the context of digital platform services provided by Malaysia takaful operators. The extended Unified Theory of Acceptance and Use of Technology (UTAUT) model is used in the study to examine this relationship. Through quantitative analysis, data were derived from an online survey with 158 respondents by using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Statistical Package for the Social Sciences (SPSS). The findings of this research contribute valuable insights to both academic and industry stakeholders. By unraveling the complex relationship between EWOM and customer satisfaction, the study offers practical recommendations for Takaful operators to enhance their digital platforms and foster positive customer experiences. As digital platforms continue to reshape the Takaful industry, this paper provides a timely and relevant analysis that aids Takaful operators in optimizing their services, fostering customer satisfaction, and sustaining their competitive edge in the evolving landscape of digital financial services.